دور الاستثمار في المشروعات الصغيرة في تحقيق الناتج الممكن في سوريه (Latakia University Journal - Economic and Legal Sciences Series, 2018)
سورية من البلدان الغنية بعوامل الإنتاج من  ثروات باطنية ورأس المال البشري وأراضي خصبة، لكن بالمقابل نجد أن الناتج المحلي الإجمالي منخفض ولا يتناسب مع وفرة هذه العوامل ولا يصل إلى الحدود الممكنة له والتي يمكن بلوغها من خلال رفع معدل النمو والذي يكون الاستثمار بشكل رئيس مسؤولا عنه حيث أن هناك سوء استخدام واضح للموارد، وانتاجية منخفضة لرأس المال، وبسبب ما تتمتع به المشروعات الصغيرة و من ميزات أهمها تأمين فرص عمل بمعدل كبير وبتكلفة منخفضة نسبيا، إضافة إلى استثمارها للموارد بالشكل الأمثل حيث أنها تمزج عوامل الإنتاج بطريقة تجعل القيمة المضافة تصل إلى حدود تكاد تكون القصوى، لاسيما اذا ما أعطيت التمويل اللازم والحماية القانونية والدعم الفني اللازم لتؤدي مهمتها على أكمل وجه. وبالتالي من الضروري بدء العمل الفعلي للمؤسسات الناظمة لعمل هذه المشروعات وإنشاء حاضنات أعمال و السعي لتحقيق التكامل بين السياسة الاقتصادية وبين برامج عمل المشروعات الصغيرة، وبالتالي يمكن أن تكون حلاً للاقتصاد السوري للوصول إلى الناتج الممكن والذي سينعكس إيجاباً على مستوى المعيشة وعلى درجة التطور والرخاء. Syria is one of the rich countries of internal resources , human capital and fertile lands . On the other hand, GDP is low and inadequate with the plenty of factors and does not reach its possible borders that cannot be accessed by raising the growth rate which is controlled by investment. that there is an obvious misuse of resources and a low productivity of the capital. SME's have many advantages such as savings ,relatively, labors with a high rate and a low cost. In addition, they ,perfectly, invest resources because they mix production factors in a way making value added almost maximum, especially if it is finance-obligated , law-protected and technique-supported .So, it is important to start the effective work of the organizing institutions which are concerned with these enterprises. In addition, it is essential to establish business incubators and aim fulfilling a completeness between the economic policy and small enterprises schedules. As a result, it could be a solution for the Syrian economy to get at the potential output which will be reflected positively on life level and prosperity status